Design of a Hybrid Animated Film on Dating from an Islamic Perspective - Msy. Pradita Indraswari. H; Saffaana Sabrina Hidayati; Dhani Agustinus (SEAN Institute, 2026)
Islam emphasizes the importance of maintaining the sanctity of the relationship between men and women before marriage and avoiding behavior that can have negative impacts on individuals and society. The purpose of this study was to determine the design of a hybrid animated film about dating from an Islamic perspective. The design method used descriptive qualitative. The results of the hybrid animated film design about dating from an Islamic perspective combine 2D and 3D animation elements to convey a message about a healthy relationship and in accordance with Islamic values.